Fatores que motivam e influenciam a demanda de pescado em Santarém no Estado do Pará - ROMA, Lucas de Andrade (Universidade Federal do Oeste do Pará, 2023)
To understand the drivers for fish consumption in the city of Santarém, Pará, and whether covid-19 and Haff disease had an influence in the last two years on the reduction in fish intake. Online questionnaires were applied through the Google Forms application. With a return of 69 questionnaires, the majority of female participants. The education of both sexes was considered high, with higher education for most collaborators (42%). The predominant religion was Catholic, with a higher percentage among women. The average per capita consumption between genders was high for the WHO recommended average (27.43 ± 31.33 kg/person/year) for households with women and (16.16 ± 18.16 kg/person/year) year) men. The taste, health and quality of the fish were the main reasons for purchasing. In addition, the participants were able to recognize a quality fish. Fairs and fishmongers were the preferred shopping places. Fish from the natural environment were preferred by women and men did not indicate a preference in relation to the origin of the fish. The most consumed species was tambaqui (Colossoma macropomum), and the other most consumed types of fish were shrimp (Macrobrachium sp.) and crab (Ucides cordatus). Covid-19 was not an impediment to non-consumption for the majority, but Haff's disease was, with most of the two groups reporting fear of the disease. And the tambaqui (Colossoma macropomum) and the pacu (Mylossoma spp., Metynnis sp., Myleus sp.) were thetarget species of reduction in this period.